In love and struggle : letters in contemporary feminism - Jolly, Margaretta (Gender and culture., 2008)
Winner of the 2009 Feminist and Women's Studies Association Book Prize Do you think I can be a feminist mother? Did I make you and your kisses up in my mind? Will you join our military protest at the gate? Will you feed the kids when I'm in prison? Are you able to forgive me for breaking off this correspondence because you are a man?During the women's movement of the 1970s and 1980s, feminists in the United States and Britain reinvented the image of the woman letter writer. Symbolically tearing up the love letter to an absent man, they wrote passionate letters to one another, exploring questions of sexuality, separatism, and strategy. These texts speak of the new interest women began to feel in one another and the new demands-and disappointments-these relationships would create. Margaretta Jolly provides the first cultural study of these letters, charting the evolution of feminist political consciousness from the height of the women's movement to today's e-mail networks. Jolly uncovers the passionate, contradictory emotions of both politics and letter writing and sets out the theory behind them as a fragile yet persistent ideal of care ethics, women's love, and epistolary art. She follows several compelling feminist relationships sustained through writing and confronts the mixed messages of the "open letter," which complicated political relations between women (such as Audre Lorde's "Open Letter to Mary Daly," which called out white feminists for their implicit racism). Jolly recovers the unsung literature of lesbianism and feminist romance, examines the ambivalent feelings within mother-daughter correspondences, and considers letter-writing campaigns during the peace movement. She concludes with a discussion of the ethical dilemma surrounding care versus autonomy and the meaning behind the burning or saving of letters. Letters that chart love stories, letters stowed away in attics, letters burnt at the end of romances, bittersweet letters written but never sent ... this fascinating glimpse into women's intimate archives illuminates one of feminism's central concerns - that all relationships are political-and uniquely recasts a social movement in very emotional terms